A simple, rapid and efficient method for essential element supplementation based on seed germination. (30th September 2020) - Deng, Benliang; Tian, Shan; Li, Shipeng; Guo, Mingxin; Liu, Hongxia; Li, Yueyue; Wang, Qianjin; Zhao, Xusheng
Highlights: Essential elements availability: a new method was established. Soaking promotes the accumulation of essential elements in germinating seed. Essential element soaking simultaneously improves antioxidant capacity. Abstract: Fertilizer application is typically used to increase the availability of essential elements. In this study, an improved method for essential element supplementation based on seed germination was established. Solutions of essential elements (Fe 2+, Zn 2+, Cu 2+, Mn 2+, SeO3 2+, or I − or their combination) were applied to germinating soybean seeds, and the contents of the essential elements in the soybean sprouts were analyzed by atomic absorption spectroscopy. Compared with the control (seeds treated with water), the contents of iron, zinc, copper, manganese, selenium, and iodine in soybean sprouts produced by germinating seeds treated with solutions containing 10 mM essential elements were approximately 10–2000 times higher. Moreover, treatment with essential element solution increased the total antioxidant capacity and content of total thiols in the soybean sprouts. This rapid and simple technique can be used to improve nutrition for humans and livestock in regions deficient in essential elements.